(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
A background study of the chemical constituents of some environmental samples - tannery complex sand, river water, river sediment and river fishes collected from the Relocated Hazaribagh Tannery Complex (RHTC) area, was carried out. In sand samples the mean values for pH, EC and soluble salts were found to be 8.49, 0.02 mS/cm and 11.72 mg/kg and the mean concentrations of elements K, Ca, Ti, Mn, Fe, Co, Zn, As, Pb, Rb and Sr were 94.8, 68.5, 16.6, 2.68, 129, 1.19, 0.23, 0.70, 0.32, 0.62 and 1.03 mg/kg, respectively. In river water samples the average concentrations of K, Ca, Mn, Fe, Zn, As, Rb, Sr, SO 4 -2, PO4 -3, Cl-1 and NO3 -1 were 13.09, 178, 0.41, 1.82, 0.073, 0.031, 0.010, 0.48, 0.057, 0.019, 15.6, 5.68 mg/l and the average values for pH, EC, DO, BOD, SS and DS were 8.02 and 0.35 mS/cm, 6.29, 4.21, 0.06, 0.36 mg/l, respectively. The elements K, Ca, Ti, Cr, Mn, Fe, Ni, Cu, Zn, As, Rb, Sr and Pb were measured in river sediment samples at the limit of 205, 155, 67, 6.02, 17.2, 798, 1.10, 1.24, 1.99, 0.31, 2.34, 2.63 and 0.35 mg/kg, respectively. In some locally available fishes like tengra, puti, baim, taki, shrimp, chanda and baila, only the elements K, Ca, Fe, Zn, Rb and Sr could be measured in all species of fishes in the range of 0.39 - 1.01, 0.68 - 2.29, 60.6 - 125, 46.3 - 174, 2.84 - 61.8 and 12.3 - 38.0% in mg/kg, respectively. In the light of the overall study, the chemical constituent levels of the environmental samples of the RHTC area at present are low and the environment is not yet contaminated. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10919 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 45-51, 2012